2002
DOI: 10.2527/2002.80112904x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microbial populations and volatile fatty acid concentrations in the jejunum, ileum, and cecum of pigs weaned at 17 vs 24 days of age

Abstract: In a series of five 17-d replicate trials, a total of 54 cannulated and 12 noncannulated pigs were used to determine the effects of weaning age (17 d or 24 d) on pH, dry matter percentage, aerobic and anaerobic microflora, lactate, and volatile fatty acid (VFA) concentrations in the jejunum, ileum, and cecum of weanling pigs. At -14 d of age, cannulated pigs were surgically fitted with T-cannulas in the jejunum (n = 20), ileum (n = 18), or cecum (n = 16). Upon weaning, cannulated pigs were individually caged i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 18 publications
11
79
2
3
Order By: Relevance
“…VFA analysis of caecal digesta was performed using gas liquid chromatography based on the method of Franklin et al (2002). Molar proportions of each of the individual acids were then calculated by dividing sample concentrations obtained for each acid by the total concentration of all six VFAs.…”
Section: Statistical Modelmentioning
confidence: 99%
“…VFA analysis of caecal digesta was performed using gas liquid chromatography based on the method of Franklin et al (2002). Molar proportions of each of the individual acids were then calculated by dividing sample concentrations obtained for each acid by the total concentration of all six VFAs.…”
Section: Statistical Modelmentioning
confidence: 99%
“…It has been reported that weaning stress dramatically decreases the amount of Lactobacillus and increases the amount of Escherichia coli present in the gut (Franklin et al, 2002;Castillo et al, 2007). A recent study reported that Lactobacillus was negatively correlated with oxidative stress, while, conversely, E. coli showed a strong positive correlation with oxidative stress in the intestines of early weaned piglets (Xu et al, 2014a).…”
Section: Introductionmentioning
confidence: 98%
“…A pig that is hungry is considered by EU guidelines to have reduced welfare in that animals should be free from hunger (EU council directive 91/630/ EEC). However, an empty GI tract may reduce the risk of accidental carcass contamination (Franklin et al, 2002). If a pig is presented to the stun with an empty stomach, this may be better for pork quality and food safety, but an empty/diminished stomach puts the pig at risk of being hungry and perhaps becoming fatigued.…”
Section: Discussionmentioning
confidence: 99%